2020
DOI: 10.1038/s41598-020-58337-4
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin S activation contributes to elevated CX3CL1 (fractalkine) levels in tears of a Sjögren’s syndrome murine model

Abstract: Autoimmune dacryoadenitis and altered lacrimal gland (LG) secretion are features of Sjögren's syndrome (SS). Activity of cathepsin S (CTSS), a cysteine protease, is significantly and specifically increased in SS patient tears. The soluble chemokine, CX3CL1 (fractalkine), is cleaved from membranebound CX3CL1 by proteases including CTSS. We show that CX3CL1 is significantly elevated by 2.5fold in tears (p = 0.0116) and 1.4-fold in LG acinar cells (LGAC)(p = 0.0026) from male NOD mice, a model of autoimmune dacry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…CTSS participated in the abdominal aortic aneurysm (AAA) formation, and inhibition of CTSS suppressed AAA formation in mice ( 29 ). A previous study showed that CTSS -mediated induction of CX3CL1 might contribute to the ocular surface and lacrimal glands inflammation in Sjögren's syndrome with a 4.5-fold increase in CX3CR1 -expressing macrophages ( 30 ). In chronic obstructive pulmonary disease, reduction in CTSS expression prevents loss of lung function, reduces inflammation, and slows the lung tissue remodeling ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…CTSS participated in the abdominal aortic aneurysm (AAA) formation, and inhibition of CTSS suppressed AAA formation in mice ( 29 ). A previous study showed that CTSS -mediated induction of CX3CL1 might contribute to the ocular surface and lacrimal glands inflammation in Sjögren's syndrome with a 4.5-fold increase in CX3CR1 -expressing macrophages ( 30 ). In chronic obstructive pulmonary disease, reduction in CTSS expression prevents loss of lung function, reduces inflammation, and slows the lung tissue remodeling ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines such as interferon-γ (IFN-γ) and tumor necrosis factor (TNF-α) are highly expressed in NOD mouse LG [ 27 ]. LGAC treated in vitro with IFN-γ exhibit characteristics of NOD mouse LGAC including reduced Rab3D [ 27 ], increased MHC II [ 27 ] and increased CX3CL1 expression [ 17 ]. Cultured LGAC exposed to IFN-γ also exhibit enhanced CTSS secretion with CCh stimulation, while β-hex release is unaffected [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin S (CTSS) is a lysosomal cysteine protease associated with many physiological processes, including extracellular matrix degradation [ 14 ], major histocompatibility complex II (MHC II) processing in antigen presentation [ 15 ] and protein catabolism [ 15 , 16 , 17 , 18 ]. Dysregulation of CTSS is implicated in multiple autoimmune diseases [ 14 ], including rheumatoid arthritis [ 19 ], systemic lupus erythematosus [ 20 ], multiple sclerosis [ 21 ] and SS [ 19 , 20 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations